'All cities are equal, but some are more equal than others'. Policy mobility and asymmetric relations in inter-urban networks for sustainability. Issue 2 (4th May 2018) - Mocca, Elisabetta
ABSTRACT: Knowledge sharing is deemed an important function of transnational municipal networks. However, in the literature on these organisations, a critical discussion of the implications of this process is scant. This article unpacks the mechanisms regulating learning, and examines the cognitive and relational dynamics of knowledge exchange within socio-ecological urban networks. By analysing the experience of a small group of European post-industrial second cities in socio-ecological urban networks, this article shows that network members exchange ideas and practices to tackle urban regeneration issues. The data suggest that, despite touted as a peer-to-peer practice, knowledge sharing reinforces asymmetrical relationships among network members, enabling the 'soft domination' of more advanced cities over less successful ones.